Estetika Di Balik Popularitas: Kajian Bentuk Musik Dalam Lagu “START” Karya Depapepe - Ibnu Yan Wiratama; Dadang Dwi Septiyan; Rian Permana (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2026)
This study aims to analyze and describe the musical form of the song “START” by Depapepe. As a highly popular and influential work in modern instrumental guitar music, “START” demonstrates a creative exploration of energetic expression and complementary harmony between two acoustic guitars without compromising its structural coherence. This study employs a qualitative methodology with a musicological approach and library research, utilizing data collection techniques such as observation, documentation, literature review, and discography studies. The findings indicate that the musical form of “START” integrates systematically organized sections developed through various motivic and phrasal manipulations. Based on these findings, it can be concluded that the musical form of “START” does not strictly adhere to classical period conventions; it does not consistently feature symmetrical question-and-answer phrasing or perfectly balanced antecedent-consequent sentences, and its chord progressions conclude with diverse cadences. This structural complexity reinforces the song's energetic and optimistic character, creating a cohesive and dynamic musical unity.